Electrochemical Study of Biotin-Modified Self-Assembled Monolayers: Recommendations for Robust Preparation - Richard J.C. Brown; Dan J.L. Brett (The Scientific World Journal)
The development of the underpinning methodology for the production of robust, well-formed, and densely packed biotin-HPDP functionalised gold surfaces, the crucial first step in immobilising bimolecules on surfaces, is described. Self-assembled monolayers (SAMs) with biotin end-groups were prepared on polycrystalline gold surfaces according to a published method. The layers formed were studied using cyclic voltammetry to determine the composition of the layer and its quality. Crystal impedance spectroscopy was also applied as a complimentary indicator of the composition of the layer.For the first time, the effect of assembly time on the properties of the layer was studied along with the composition of the layer and the ability of the precursor molecule to self-assemble by oxidative addition.